PENERAPAN PENDEKATAN BEHAVIORISTIK DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL ALQURAN SANTRI - MUTTAQIN, MUTTAQIN (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2024)
Application of the Behavioristik approach is the theory that his discussion is about patterns of human behavior which in this case is to memorize the qur'an, which is one of the most glorious worship activities run by a Muslim, from all walks of life be it male or female adults or even children, in this study the researchers raised the research Application form fokos Approach Behavioristik in improving the ability of Memorizing the Quran Naat in the hut Qur'anic Tahfidh boarding school children An